Daughters of fire - Erskine, Barbara (London HarperCollins Publishers Ltd, 2007)
The sweeping new novel from the bestselling author of LADY OF HAY switches between Roman Britain and the present day where history dramatically impacts on the lives of three women
1
Keywords: Historical drama; Women